Gluten serological testing in various dog breeds with paroxysmal dyskinesia - Rogers, Casey B.; Meyerhoff, Nina; Volk, Holger A. (Frontiers in Veterinary Science, 2023)
Background Paroxysmal gluten-sensitive dyskinesia is a subtype of movement disorder classified as canine paroxysmal dyskinesia (cPD), which until now has only been described in Border Terriers (BT). Objectives Our aim was to report cPD with positive gluten serology in dog breeds other than BT. Animals Thirty-one client-owned dogs with suspected cPD were examined in this study. Methods The hospital records of the dogs where the serum was tested for modified gliadin peptide immunoglobulin G (gliadin IgG) and tissue transglutaminase-2 immunoglobulin A (transglutaminase-2 IgA) were studied. A total of 31 dogs were presented to the clinic with cPD. A work-up consistent with Tier 1 or Tier 2 confidence levels for canine epilepsy was undertaken in all dogs. The dogs' diets and episode descriptions or videos in 16/31 cases were additionally studied. A follow-up was held to inquire about the dogs' wellbeing and response to the diet changes. Results Fourteen of the 31 dogs tested positive for gluten sensitivity with either gliadin IgG or transglutaminase-2 IgA or both ratios elevated. In seven dogs, serology was classified as questionable with gliadin IgG or transglutaminase ratios mildly elevated. Ten dogs tested negative. According to the owners' reports, five of the dogs that tested positive had no more episodes after changing to a strictly gluten-free diet, with one of the dogs relapsing twice after being fed treats containing gluten. Three dogs had a reduction in episode frequency of >50%, and two dogs had shorter and less intense episodes. Conclusion A considerable subset of dog breeds presented for presumed cPD showed laboratory signs of gluten sensitivity and responded to a gluten-free diet.